THE FUTURE OF SUSTAINABLE FORESTRY: BIOMOLECULAR ADVANCES AND CONSERVATION STRATEGIES - Clara Mendes; Pedro Silva; Tigran Sargsyan (Yayasan Adra Karima Hubbi, 2025)
Sustainable forestry is increasingly crucial for maintaining biodiversity and ecosystem services in the face of climate change and deforestation. Advances in biomolecular techniques offer innovative solutions for enhancing forest conservation and management practices. This study aims to explore the potential of biomolecular advances in promoting sustainable forestry practices and effective conservation strategies. By examining the integration of molecular biology with traditional forestry techniques, the research seeks to identify key innovations that can improve forest resilience and sustainability. A comprehensive literature review was conducted, focusing on recent biomolecular technologies such as genetic engineering, DNA barcoding, and molecular markers. Case studies from various regions were analyzed to evaluate the application of these techniques in forest conservation and management. Findings indicate that biomolecular advances significantly enhance the ability to monitor forest health, assess biodiversity, and implement targeted conservation strategies. Techniques such as genetic modification of tree species for disease resistance and the use of molecular markers for population genetics have shown promising results in improving forest resilience. This research underscores the importance of integrating biomolecular technologies into sustainable forestry practices.